Automatic Door Based on Radio Frequency Identification (RFID) and Password in Electrical Engineering Laboratory - Syahid Syahid (Politeknik Negeri Semarang, 2019)
RFID (Radio Freq uency Identification) systems are used as personal identification cards in the room access system especially in Electrical Engineering Laboratory. This system is intended to maintain the security and privacy of the room from someone who does not have the authority to enter the room. This security system uses a two-tier security system, namely through an RFID identity card and security code. The design and implementation of this system, an electric key work system is evaluated based on the solenoid component and the password used when accessing the room. RFID tags used in this system are in the form of